Aboriginal Social Work Education in Canada: Decolonizing Pedagogy for the Seventh Generation - Sinclair, Raven (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2019)
Aboriginal social work is a relatively new ﬁeld in the human services, emerging out of the Aboriginal social movement of the 1970s and evolving in response to the need for social work that is sociologically relevant to Aboriginal people. Aboriginal social work education incorporates Aboriginal history and is premised upon traditional sacred epistemology in order to train both Aboriginal and non-Aboriginal social workers who can understand and meet the needs of Aboriginal people. The deﬁciencies of contemporary cross-cultural approaches and anti-oppressive social work education are highlighted as a means to emphasize the importance of social work education premised upon relevant history and worldview. The values and responsibilities that derive from Aboriginal worldview as the foundation for Aboriginal social work education are discussed in terms of the tasks that are implied for the educator and student of Aboriginal social work. Such tasks include self-healing, decolonization, role modelling, developing critical consciousness, and social and political advocacy. Aboriginal social work education, a decolonizing pedagogy directed to mitigating and redressing the harm of colonization at the practice level, is a contemporary cultural imperative.